Suppression des quotas et nouvelles formes de régulation de l’économie laitière : les conditions patrimoniales du maintien de la production laitière en montagne - Marie Dervillé; Perrine Vandenbroucke; Gilles Bazin (Revue de la Régulation)
With the abolition of the quota system, dairy farmers loose a competition management tool among producers and between areas that questions the future of mountain dairy farming. This paper discusses the conditions for its preservation related to its heritage. Three forms of regulation are considered: market segmentation and the development of quality chains based on a logic of identity, integration of measures specific for mountain dairy farmers in the common agricultural policy and the support given by local authorities to their agriculture. They are analysed based on a patrimonial economics’ framework aiming at identifying the object of identity, the resources instituted into a heritage, the communities underlying these processes and their ability to help dairy farms to gain foothold in the mountains. With the quota system, dairy markets were under the control of political forces. The alternative forms of patrimonial regulations exercise a regional (market segmentation) or partial (agro-environmental and mountain policy as well as the institution of agriculture by local players into a patrimony) limitations over market competition rules. This shift, in the monitoring capacity of markets from European and national to local level, opens the way to a differentiation of economic models and raises the question of financial resources and skills available locally to put them in place.